Marketing de relacionamento no futebol: o programa sócio-torcedor do Sport Club Corinthians Paulista - Martins, Fabiano Fernandes (2016)
The cultural and socio-economic importance of football in the country is portrayed in the Brazilian daily. The sport exhibition has great space in all forms of communication and has been a strategic partner to transmit the messages from different companies. In this context, the demand for sports marketing has grown each year and football has become a major player. However, sports organizations increasingly need of revenue to keep doing football entertainment, an event and an attractive sport. This is the moment where relationship marketing, through partner programs fans, reveals a great ally. Through a case study of the relationship and loyalty program of the Sport Club Corinthians Paulista, called Faithful Fan, it was revealed that the socio fan program creates differentiation, loyalty and strengthens the sports brand, becoming a powerful means of consumer supporter transformation